The city and its dynamics (Orinoquia, 2014)
The accelerated growth of the cities with over a million of inhabitants has ceased in the last fifty years. However, in the last decade those ones with less than hundred thousand (inhabitants), and the ones that range between 500 thousand and a million inhabitants, have grown and face new challenges related to the population growth, the unplanned urban expansion, the lack in coverage of public services, the urban pollution and in general to the dynamics of the economic and demographic relationships that settle there (Stren R, 1995; Borja J, 2003; UN, 2010). In the regional context, Colombia is one of the most populated countries and with higher urban concentration in the continent, with a population of 47.661.368, according to 2005 census projections, 30% of which congregate among five cities, with a 2,3% of expectative of population growth (DANE, 2010). In 2009, the country was classified as the third most populated country of Latin America, fifth in urban population growth rate and third in South America on having the higher amount of cities of over a million inhabitants (Ordoñez M, 2009).